The effect of ventricular pre-excitation on ventricular wall motion and left ventricular systolic function. Issue 7 (9th August 2017) - Dai, ChenCheng; Guo, BaoJing; Li, WenXiu; Xiao, YanYan; Jin, Mei; Han, Ling; Dong, JianZeng
Abstract: Aims: The relationship between ventricular pre-excitation and left ventricular dysfunction has been described in the absence of sustained supraventricular tachycardia in a series of case reports. There have been no systematic studies about the effect of ventricular pre-excitation with different accessory pathway locations on ventricular wall motion and left ventricular (LV) systolic function. Methods and results : Thirty patients were selected for each of 4 groups, including those with right septal pathways (Group 1), right free-wall pathways (Group 2), left free-wall pathways (Group 3), and non-pre-excited patients undergoing electrophysiological evaluation for supraventricular tachycardia. We analysed the influence of the location of the accessory pathway on ventricular wall motion, systolic function, ventricular synchronism, and LV size. Right-sided accessory pathways were associated with abnormal motion of the interventricular septum, LV dyssynchrony, decreased LV systolic function, and increased LV diameter. Eighteen of 60 cases (30.0%) with right-sided accessory pathways had LV dyssynchrony, and these patients had lower LV ejection fraction and higher LV end-diastolic diameter. Conclusion : Right-sided accessory pathways may impair ventricular wall motion and LV systolic function, resulting in decreased LV ejection fraction and increased LV end-diastolic diameter. These effects occurred in patients with LV dyssynchrony. These effects, including LV dyssynchrony, resolved after radiofrequency ablation. A right-sided free-wall accessory pathway may have more detrimental effects than a septal accessory pathway. Left ventricular dyssynchrony and abnormal interventricular septal motion appeared to be responsible for the pathogenesis of LV dysfunction and remodelling.